Cognitive function, mood and sleep changes in response to a Tai Chi/Qigong intervention among older breast cancer survivors: an exploratory analysis - James, Dara L.; Maxfield, Molly; Han, SeungYong; Hawley, Nanako A.; Petrov, Megan E.; Sears, Dorothy D.; Vance, David E.; Larkey, Linda K. (Frontiers in Cognition, 2024)
Cognitive decline is a significant, persistent issue among breast cancer survivors (BCSs) affecting more than 50% and greatly impacting health and well-being, particularly among those who are aging. Scalable, lifestyle interventions to mitigate cognitive decline in this population are needed. This study aimed to explore the effects of Tai Chi Easy (TCE) on perceived cognition function among older BCSs. Methods. The current work was part of a larger NCIfunded trial (R01CA182901, primary results reported elsewhere). Female BCSs, aged 45-75 years, were randomized to one of three conditions: two active interventions, Tai Chi Easy (TCE) or sham Qigong (SQG), or an education control group (EDC). In this exploratory analysis of older female participants (aged 60-75y), perceived cognitive function and performance and related factors (including anxiety, depression, and insomnia symptom severity) were examined. We anticipated TCE and SQG would show greater improvements in perceived cognitive function and performance compared to EDC. Results. A total of 75 female BCS were included in the analysis (TCE=23; SQG=22; EDC=30). Linear mixed model results showed BCS randomized to TCE and SQG reported improvements in perceived cognitive impairment and cognition-related effects on quality of life relative to EDC (with small to medium effect sizes; Cohen's d= 0.46 and 0.76), whereas no results were found for cognitive performance measures. Relative to EDC, TCE did not exact changes in depression, anxiety, and insomnia symptom severity; however, SQG showed decreases in depression and insomnia symptom severity (with corresponding small to medium effect sizes, Cohen's d= -0.36 and -0.56). Discussion. Findings from the current exploratory study suggest that low-exertion, gentle exercise, with or without breath and meditative focus, may improve perceived cognitive function, and, that without breath and meditative focus, may improve depressed mood and insomnia symptoms among older BCS. These promising findings may have immediate and long-term implications on accessible treatment options recommended by geriatricians and oncologists treating older BCS at an elevated risk for cognitive impairment.